Hearing in action; auditory properties of neurons in the red nucleus of alert primates - Lovell, Jonathan M.; Mylius, Judith; Scheich, Henning; Brosch, Michael (Frontiers in Neuroscience, 2014)
The response of neurones in the Red Nucleus pars magnocellularis (RNm) to both tone bursts and electrical stimulation were observed in three cynomolgus monkeys (Macaca fascicularis), in a series of studies primarily designed to characterise the influence of the dopaminergic ventral midbrain on auditory processing. Compared to its role in motor behaviour, little is known about the sensory response properties of neurons in the red nucleus; particularly those concerning the auditory modality. Sites in the RN were recognised by observing electrically evoked body movements characteristic for this deep brain structure. In this study we applied brief monopolar electrical stimulation to 118 deep brain sites at a maximum intensity of 200 µA, thus evoking minimal body movements. Auditory sensitivity of RN neurons was analysed more thoroughly at 15 sites, with the majority exhibiting broad tuning curves and phase locking up to 1.03 kHz. Since the RN appears to receive inputs from a very early stage of the ascending auditory system, our results suggest that sounds can modify the motor control exerted by this brain nucleus. At selected locations, we also tested for the presence of functional connections between the RN and the auditory cortex by inserting additional microelectrodes into the auditory cortex and investigating how action potentials and local field potentials were affected by electrical stimulation of the RN.